2019
DOI: 10.1186/s12967-019-02136-7
|View full text |Cite
|
Sign up to set email alerts
|

The impact of cryopreservation on bone marrow-derived mesenchymal stem cells: a systematic review

Abstract: Mesenchymal stem cells (MSCs) represent an invaluable asset for the field of cell therapy. Human Bone marrow-derived MSCs (hBM-MSCs) are one of the most commonly used cell types in clinical trials. They are currently being studied and tested for the treatment of a wide range of diseases and conditions. The future availability of MSCs therapies to the public will require a robust and reliable delivery process. Cryopreservation represents the gold standard in cell storage and transportation, but its effect on BM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
100
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(109 citation statements)
references
References 90 publications
8
100
1
Order By: Relevance
“…It is necessary to point out that frozen bone marrow was used for the MSC derivation. Nevertheless, it has been reported in the literature that cryopreservation does not affect BM-MSC morphology, expression of surface markers, or proliferation and differentiation potential [59]. However, the effects on viability, migration, attachment, genomic stability and paracrine secretion remain undefined due to the variability in the cryopreservation process and to the lack of standardized assays.…”
Section: Discussionmentioning
confidence: 99%
“…It is necessary to point out that frozen bone marrow was used for the MSC derivation. Nevertheless, it has been reported in the literature that cryopreservation does not affect BM-MSC morphology, expression of surface markers, or proliferation and differentiation potential [59]. However, the effects on viability, migration, attachment, genomic stability and paracrine secretion remain undefined due to the variability in the cryopreservation process and to the lack of standardized assays.…”
Section: Discussionmentioning
confidence: 99%
“…Current cryopreservation methods store cells in suspension in cryopreservation solutions below −135 • C [6]. The process of cooling and thawing, as well as the influence of the cryopreservation agents, can lead to damage and alteration of the desired function of the MSCs [7,8]. Cooling rate is one of the largest influencers in a successful cryopreservation process; freezing at a rate that is considered too slow causes dehydration of the cell with associated stresses and increases the osmotic imbalances as the solutes are excluded from the ice crystals potentially exposing cells to toxic concentrations, although the possibility of intracellular ice is reduced [6,22,25].…”
Section: Discussionmentioning
confidence: 99%
“…Long term storage generally occurs at temperature less than −135 • C [6]. Yet, this cryopreservation can alter MSC function and consequently may lose their therapeutic potential [7,8]. There are several factors that interfere with cryopreservation, such as fluctuation in the temperature of ice nucleation, inadequate cryopreservation agent concentrations and thawing rate [9].…”
Section: Introductionmentioning
confidence: 99%
“…DMSO in the cryopreservation uid substantially increased the viability of synovial MSCs. A systematic review of 41 in vitro studies of bone marrow MSCs by Bahsoun et al showed that cryopreservation does not affect the morphology, expression of surface markers, differentiation, or proliferative potential, but the effects on viability and colony-forming capacity remain to be determined [29]. Variations in viability were mainly related to differences in the cryopreservation solutions, including the DMSO concentrations, and differences in methods used to measure viability.…”
Section: Discussionmentioning
confidence: 99%